AN APPLICATION OF THE EXPERIMENTAL CHOICE MODEL TO ESTIMATE PREFERENCES FOR OUTDOOR RECREATION ATTRIBUTES IN TAMAN NEGARA MALAYSIA NATIONAL PARK - SHUIB, AHMAD (ASEAN Journal on Hospitality and Tourism, 2006)
The main objective of the study is to explore the applicability of the choice experiment method to reveal preferences of visitors. The preferences are related to the attributes of eco-tourism resources in Taman Negara Malaysia. Four alternative sets of combinations of attributes which included types of accommodation, congestion levels, permitted length of stay per permit and entrance fees are given to visitors to choose. The results of the analysis on the probability of choice function reveal that types of accommodation, indicated by differences in room rates, and congestion levels are the two significant factors influencing visitors preferences for the eco-tourism resources. The choice of types of accommodation facilities can be implied to the preferences for quality services and facilities. On the other hand, the congestion level is associated with lower entrance fee and costs of visits.